Value, Cost, and Marginal Utility - Böhm-Bawerk, Eugen von (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
In this article of fundamental importance to the comprehension of the historical stance of the Austrian economists concerning the relationship between value, cost, and marginal utility, the author answers to the criticism elaborated by Heinrich Dietzel against the theorists of the marginal value. The author also discusses the scientific status of the theory of value at the end of the 19th century.